Habitats, nécropoles et paysages dans la moyenne et la basse vallée du Rhône (viie-xve s.) Contribution des travaux du TGV-Méditerranée à l'étude des sociétés rurales médiévales - Maufras, Odile (Documents d'archéologie française, 2006)
The plan to extend the TGV high-speed rail link from Lyon to Marseille was a major scientific challenge, comprising 300 km of transect through archeologically highly-sensitive areas and notably the Rhone corridor - a key western European trunk route since prehistoric times. A rescue operation unprecedented in terms of its size and complexity was initiated to take up the challenge and in this volume, Odile Maufras presents the results of the campaign covering the medieval period. No less than 14 separate digs focused on sites of non-village rural occupation from the seventh to the fifteenth centuries. The sites are first described in a series of concise monographs whose standardized layout will help readers easily find their way. The second part studies key environmental aspects, material culture and cultural practices in a series of well-documented and presented overviews and analytical articles. The work throws new light on the sort of isolated habitats which are generally so difficult to pinpoint and updates the geographical and environmental picture of the central Rhone valley. It returns to the question of a break between late Antiquity and the Middle Ages, while at the same time refining our knowledge of organizational development in the countryside.